Variation in Institutional Review processes for a multisite observational study - Vick, Catherine C.; Finan, Kelly R.; Kiefe, Catarina; Neumayer, Leigh; Hawn, Mary T. (The American journal of surgery, 2005)
The Veterans Administration is an ideal setting for multisite studies; however, individual VA Institutional Review Board (IRB) approval is necessary. This study examines the burden of multisite IRB approval on a Health Services Research and Development (HSRD) ventral hernia outcomes observational study. Data gathered on the IRB process per site included time required for application completion, staff training and compliance, IRB affiliation (VA or university), approval status, and time to IRB approval. Wilcoxon rank sum tests were used to determine differences in median times for application completion and approval. Financial and temporal expenses were calculated. Significant differences were found in median time to complete applications by IRB affiliation ( P < .01) and median time to approval by changes required to the consent letter ( P < .05). The IRB process for a multisite observational study is expensive in both time and money. A VA national IRB for multisite studies would significantly decrease the financial and temporal burden for observational studies.